Complete human CD1a deficiency on Langerhans cells due to a rare point mutation in the coding sequence - Cerny, D; Thi Le, D; The, T; Zuest, R; Kg, S; Velumani, S; Khor, C; Mori, L; Simmons, C; Poidinger, M; Zolezzi, F; Ginhoux, F; et al. (Elsevier, 2016)
CD1a molecules on skin Langerhans cells that present self and microbial lipids to T cells have been implicated in the maintenance of skin barrier function. We identified two healthy Vietnamese siblings with a complete lack of surface CD1a expression. Both individuals showed a rare single nucleotide polymorphism (SNP) rs761269454 resulting in a Leu to Pro mutation in the α3 domain of CD1a. Recombinant CD1a-L285P expressed in human cell lines reproduced the defect observed in primary DCs. The defect was only apparent when another rare SNP, rs538916791, introduced a stop codon in the second allele of CD1a. The lack of CD1a expression did not result in any apparent skin abnormalities, or in systemic immune impairment in either individual.